DEVELOPING E-MODULE OF WAQF LITERARY TO THE IAIN PONTIANAK STUDENTS - Heriansyah, Heriansyah; Aunurrahman, Aunurrahman; Radiana, Usman (Khatulistiwa, 2024)
This study aims to develop e-modul of waqf literary to the students of State Institute for Islamic Studies of Pontianak (IAIN Pontianak). Research and Development method with ADDIE model was used in this study. There are five steps of ADDIE model were implemented in this study, that is, (1) Analyze, (2) Design, (3) Develop, (4) Implement, and (5) Evaluate. There were 30 Sharia (law) students involved as the subject of the study. Besides, there were also six experts as the validators, they are: design expert, subject matter expert, and media expert. The questionnaire was used as the instrument of collecting data, and the results